Expression of Human Skin-Specific Genes Defined by Transcriptomics and Antibody-Based Profiling. (February 2015) - Edqvist, Per-Henrik D.; Fagerberg, Linn; Hallström, Björn M.; Danielsson, Angelika; Edlund, Karolina; Uhlén, Mathias; Pontén, Fredrik
To increase our understanding of skin, it is important to define the molecular constituents of the cell types and epidermal layers that signify normal skin. We have combined a genome-wide transcriptomics analysis, using deep sequencing of mRNA from skin biopsies, with immunohistochemistry-based protein profiling to characterize the landscape of gene and protein expression in normal human skin. The transcriptomics and protein expression data of skin were compared to 26 (RNA) and 44 (protein) other normal tissue types. All 20, 050 putative protein-coding genes were classified into categories based on patterns of expression. We found that 417 genes showed elevated expression in skin, with 106 genes expressed at least five-fold higher than that in other tissues. The 106 genes categorized as skin enriched encoded for well-known proteins involved in epidermal differentiation and proteins with unknown functions and expression patterns in skin, including the C1orf68 protein, which showed the highest relative enrichment in skin. In conclusion, we have applied a genome-wide analysis to identify the human skin-specific proteome and map the precise localization of the corresponding proteins in different compartments of the skin, to facilitate further functional studies to explore the molecular repertoire of normal skin and to identify biomarkers related to various skin diseases.